AB1299 AN ONGOING ANTICENTROMERE ANTIBODY RESPONSE ASSOCIATES WITH PROGRESSION TOWARDS SYSTEMIC SCLEROSIS. (June 2019) - Leeuwen, Nina van; Boonstra, Maaike; Bakker, Jaap; Wortel, Corrie; Scherer, Hans Ulrich; Toes, Rene; Huizinga, Thomas; Vries-Bouwstra, Jeska de
Abstract : Background: Although some dated studies suggest a possible association between clinical characteristics and isotypes of anticentromere antibodies (ACA) in patients with systemic sclerosis (SSc), characteristics of ACA have not been described thoroughly in SSc. Objectives: Describe characteristics of anticentromere antibody (ACA) response in a large cohort of SSc patients. Evaluate differences between ACA response between SSc patients fulfilling ACR 2013 criteria and those with very early diagnosis of SSc (VEDOSS). Methods: ACA IgG, IgM and IgA levels were assessed in serum samples of patients visiting the Leiden SSc care pathway and who were IgG ACA+ at baseline. Patients had to fulfil either the ACR criteria or the VEDOSS criteria. Differences in isotype expression and levels between the two groups were evaluated, also with stratification for disease duration. Furthermore, in the SSc group we determined correlations between isotypes and disease duration and evaluated if isotype positivity was associated with clinical manifestations. Results: ACA characteristics were measured in 167 ACA IgG+ patients. Thirty-five patients (21%) fulfilled the VEDOSS criteria and 132 (79%) the ACR criteria. ACA IgG+ patients displayed a broad isotype usage with 75% being ACA IgA+ and 68% being ACA IgM+ in serum. Patients within the SSc group showed higher ACA IgG levels and a higher percentage of ACA IgM positivity compared to the VEDOSS patients. Notably, these findings remained valid after stratification for disease duration, demonstrating that VEDOSS patients that did not progress to SSc within at least 5 years had lower ACA IgG levels and were less frequently positive for ACA IgM. In the SSc group, moderate correlations between isotypes were found; ACA IgM positivity was associated with occurrence of digital ulcers (p=0.02). Conclusion: We observe a clear difference in the quality of the centromere-specific immune response between VEDOSS patients and SSc patients, also when stratifying for disease duration. The higher ACA IgG levels and presence of ACA IgM in SSc patients indicates that the ACA response in SSc is more pronounced showing signs of ongoing activity. These data indicate that the ACA B cell response is potentially relevant in disease development. In addition, ACA isotype expression and ACA IgG levels might contribute to better identify VEDOSS patients at risk for SSc development. Disclosure of Interests: Nina van Leeuwen: None declared, Maaike Boonstra: None declared, Jaap Bakker: None declared, Corrie Wortel: None declared, Hans Ulrich Scherer Grant/research support from: Sanofi, BMS, Rene Toes Grant/research support from: Sanofi, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Jeska de Vries-Bouwstra: None declared